1978
DOI: 10.1111/j.1432-1033.1978.tb12118.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Abnormalities in Fucosidosis. Characterization of a Disaccharide and Two Glycoasparagines

Abstract: The urinary excretion of fucose‐containing material was found to be highly increased in a patient with fucosidosis type 2. Three structurally related compounds, a disaccharide and two glycoasparagines, were isolated from the urine. The isolation procedure included ultrafiltration. gel chromatography on Sephadex G‐25, preparative zone electrophoresis and paper chromatography. From structural studies including optical rotation, sugar analysis, methylation analysis, ninhydrin degradation, reduction with lithium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 29 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…Strecker and co-workers (1977b) described 9 oligosaccharides and glycopeptides isolated from two patients. Recent studies by Lundblad et al (1978 a) confirmed the structures of at least two of the fuco-oligosaccharides reported by Strecker's group and in addition a new glyc0asparagine compound was isolated. A report of the first French-Canadian case by Ng Ying Kin and Wolfe (1979) gave further evidence of fucoglycoasparagine-linked oligosaccharide excretion and they suggested that this may be the result of an incomplete catabolism of human plasma a~-acid glycoprotein.…”
Section: Fucosidosissupporting
confidence: 64%
“…Strecker and co-workers (1977b) described 9 oligosaccharides and glycopeptides isolated from two patients. Recent studies by Lundblad et al (1978 a) confirmed the structures of at least two of the fuco-oligosaccharides reported by Strecker's group and in addition a new glyc0asparagine compound was isolated. A report of the first French-Canadian case by Ng Ying Kin and Wolfe (1979) gave further evidence of fucoglycoasparagine-linked oligosaccharide excretion and they suggested that this may be the result of an incomplete catabolism of human plasma a~-acid glycoprotein.…”
Section: Fucosidosissupporting
confidence: 64%
“…3a. Of the eight fucosylated oligosaccharides detected, three have already been previously shown to be related to fucosidosis [2, 29, 30, 37, 44].
Fig.
…”
Section: Resultsmentioning
confidence: 94%
“…The set of 54 glycans was established by manual assignment of glycan species from all HPAEC-MS(/MS) data. This set includes glycans described previously in literature for the LSDs included in this study [2, 9, 15, 16, 25, 29–40] as well as the glycans found previously for galactosialidosis samples [26]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucosylated glycolipid (44,255), proteoglycans (74), oligosaccharides, and glycopeptides (126,159,236,237,256) are some of the accumulating glycoconjugates characteristic of fucosido sis. Oligosaccharide and glycopeptide storage appears nearly ubiquitous in all visceral tissue (256), including cultured skin fibroblasts (254).…”
Section: Glycoprotein Storage Productsmentioning
confidence: 99%